The Role of Local Bupivacaine Irrigation in Postoperative Pain Control After Augmentation Mammoplasty: A Systematic Review and Meta-Analysis. Issue 1 (February 2017) - Qiu, Shan Shan; Roque, Marta; Chen, Yi-Chieh
Background: The objective of this study is to analyze the efficacy of local bupivacaine irrigation after augmentation mammoplasty for the control of postoperative pain. Methods: A systematic review and meta-analysis was conducted including all randomized controlled trials (RCTs) that compared the irrigation of bupivacaine (±ketorolac) versus normal saline or no irrigation for pain control after breast augmentation. The primary outcome was postoperative pain measured by visual analog scale. The study protocol was established a priori according to the recommendations of the Cochrane Collaboration. A bibliographical search was conducted in September 2015 in the following Cochrane Library databases: CENTRAL, MEDLINE, EMBASE, and Scielo. The strategy used for the search was ((augmentation AND ("mammoplasty"[MeSH Terms] OR "mammoplasty")) OR (("breast"[MeSH Terms] OR "breast") AND augmentation)) AND (("pain, postoperative"[MeSH Terms])). Results: Four RCTs with a total of 264 participants were included. Two trials compared bupivacaine alone versus placebo (normal saline or no irrigation) and 3 trials compared bupivacaine plus ketorolac versus placebo. The combined irrigation of bupivacaine and ketorolac showed a clinically significant reduction of pain in the first postoperative hour and on postoperative day 5. The irrigation with bupivacaine compared with placebo significantly reduced pain assessed on postoperative day 4. Conclusion: The irrigation of bupivacaine with or without ketorolac was associated with a reduction of postoperative pain compared with control groups for the first 5 postoperative days. Due to the few number of trials included, these results should be correlated further clinically.